Study on the Oxidative Leaching of Uranium from the Lignite in the CO32-/HCO3- System - Y. Ning; Y. Li; Y. Zhang; P. Tang (Geofluids)
Na2CO3/NaHCO3 mixtures with different oxidants were used to leach uranium in the lignite which was obtained from Lincang, Yunnan province. The experimental results showed that the optimal solid/liquid ratio and CO32-/HCO3- ratio for uranium leaching were 1 : 20 (g/mL) and 2 : 1, respectively. With the increase of carbon concentration from 0.1 mol/L to 1.1 mol/L, the leaching efficiency of uranium increased from 14.64% to 42.39% after 6 h leaching. The oxidants could significantly enhance the uranium leaching efficiency, which was up to 72.23% by injecting O2 at 1.5 L/min after 12 h leaching. The oxidative leaching process of uranium from the lignite was better fitted to the pseudo-second-order reaction model. The sequential extraction results illustrated that the oxidants could effectively enhance the leaching of organic matter bound uranium in the lignite, which was decreased from 76.86 mg/kg to 9.00 mg/kg by injecting O2. The infrared spectrum analysis demonstrated that the corresponding transmittance at about 3197 cm−1 was prominently reduced after the oxidative leaching, which intimated that the phenolic and alcoholic hydroxyl might be the main functional groups combined with uranium in the lignite.